2019
DOI: 10.1016/j.eclinm.2019.05.009
|View full text |Cite|
|
Sign up to set email alerts
|

Therapeutic Vaccination Refocuses T-cell Responses Towards Conserved Regions of HIV-1 in Early Treated Individuals (BCN 01 study)

Abstract: Background Strong and broad antiviral T-cell responses targeting vulnerable sites of HIV-1 will likely be a critical component for any effective cure strategy. Methods BCN01 trial was a phase I, open-label, non-randomized, multicenter study in HIV-1-positive individuals diagnosed and treated during early HIV-1 infection to evaluate two vaccination regimen arms, which differed in the time (8 versus 24 week) between the ChAdV63.HIVconsv prime and MVA.HIVconsv boost vaccin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
66
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 58 publications
3
66
0
1
Order By: Relevance
“…This rapid viral rebound after treatment interruption is due to the existence of a latent viral reservoir and the inability of the immune system to effectively contain viral replication. To date, numerous strategies have been pursued to achieve a functional cure or virus eradication, including early ART initiation, ART intensification (2)(3)(4)(5)(6), passive administration of antibodies (7), therapeutic vaccination (8)(9)(10)(11)(12)(13) and gene therapy (14,15), among others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This rapid viral rebound after treatment interruption is due to the existence of a latent viral reservoir and the inability of the immune system to effectively contain viral replication. To date, numerous strategies have been pursued to achieve a functional cure or virus eradication, including early ART initiation, ART intensification (2)(3)(4)(5)(6), passive administration of antibodies (7), therapeutic vaccination (8)(9)(10)(11)(12)(13) and gene therapy (14,15), among others.…”
Section: Introductionmentioning
confidence: 99%
“…The proof-of-concept BCN02 trial evaluated a kick&kill strategy that combined the HIVconsv T-cell vaccines with the HDACi RMD in a cohort of early-treated, HIV-1infected individuals. Fifteen participants of BCN01 (12), who previously received simian adenovirus-vectored vaccine ChAdV63.HIVconsv and MVA.HIVconsv, were invited 2-3 years later to receive two more dosing of the MVA.HIVconsv vaccine before (MVA 1 ) and after (MVA 2 ) three weekly-doses of RMD (RMD 1−2−3 ) followed by a monitored antiretroviral pause (MAP) for a period of 32 weeks (NCT02616874). The combined strategy was proven to be safe and vaccination was highly immunogenic.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have highlighted the fact that rAd vaccines can be used effectively as therapeutics. Studies have shown that rAd vaccines can accelerate the control of tuberculosis, they can be used to refocus T cell responses towards conserved HIV-1 epitopes and have shown efficacy in preclinical trials to resolve hepatitis C virus in a rat model where viremia was terminated within 14 days of virus challenge [36][37][38]. In addition, there have been many attempts to modify rAd vaccines to improve vaccine efficacy and oncolytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…This was not the case following HIVconsv vaccination, which induced prominent Pol epitope responses directly proportional to the relative length of the Pol segment in the HIVconsv sequence (Table 3). These results would support the ability of a potent vector delivery to (re)focus immune responses including CD4 + T cells toward regions that are generally subdominant in natural HIV-1 infection [59,60]. A different study reported over half of tested variant peptides not being recognized by CD4 + T cells [51], emphasizing even for the more promiscuous HLA class II molecules peptide selectivity and the importance of focusing on and matching vaccine responses to less variable regions of the HIV-1 proteome.…”
Section: Discussionmentioning
confidence: 63%